Agreement for Advisory Services on Assistance to the Romanian Ministry of Regional Development and Public Administration on Harmonizing State- and EU-Funded Projects in Regions - World Bank Group (World Bank, Washington, DC, 2016)
The 2014-2015 Romania Regional Development 2 Program is the continuation of the World Bank’s technical assistance to the Ministry of Regional Development and Public Administration (MRDPA). Building on the previous engagement, the current work addresses a fundamental question: given Romania’s persistent development challenges, how can the country do more with less when it comes to the public infrastructure it needs? The key is to enhance coordination and harmonization of different funding sources, particularly infrastructure programs financed from the state budget and from EU structural funds. The National Local Development Program (PNDL), managed by the MRDPA, is reviewed in depth, though the conclusions typically hold for all state-budget-funded programs. This synthesis report summarizes the main findings and recommendations from eight final reports and 24 knowledge sharing workshops organized in all eight regions in Romania in 2015. Several ‘bonus’ outputs were also produced, going beyond the terms of this technical assistance (three investment guides, an applicant guide, and an operational manual). This synthesis report – along with all the outputs it draws from – is meant as a practical tool for policymakers at the national, regional, and local level. It also seeks to inform a broader audience of private and nongovernmental stakeholders.